BONE HEALTH IN SUBJECTS WITH TYPE 1 DIABETES FOR MORE THAN 50 YEARS - Maddaloni, Ernesto (Acta Diabetol, 2017)
AIMS: Few data regarding prevalence of and risk factors for poor bone health in aging individuals with long-standing T1D are available. In this study we aim to describe the prevalence of bone fragility and to identify factors associated with low bone density in individuals with long term T1D. METHODS: We examined the prevalence of non-vertebral fractures in 985 subjects enrolled in the Joslin 50-Year Medalist Study, and measured bone mineral density (BMD) by dual-energy X-ray absorptiometry at the femoral neck, lumbar spine and radius in a subset (65 subjects, mean age 62.6 years, duration 52.5 years, HbA1c 7.1%) with no significant clinical or demographic differences from the rest of the cohort. RESULTS: Medalists have low prevalence of fractures (0.20% hip and 0.91% wrist) and normal Z-score values (spine +1.15, total hip +0.23, femoral neck −0.01, radius +0.26; p>0.05 for differences vs 0 at all sites). A significant relationship was found between lower BMD and higher total cholesterol, triglycerides and LDL levels, but not HbA1c. Low BMD at the femoral neck was associated with cardiovascular disease after adjustment for confounding factors: prevalence risk ratio (RR) [95% CI] of 4.6 [1.2–18.1], p=0.03 of CVD. No other diabetic vascular complication was found to be associated with low BMD. CONCLUSIONS: These are the first data regarding bone health in aging individuals with T1D for more than 50 years. The low rates of non-vertebral fractures and the normal Z-score suggest the long T1D diabetes duration did not increase the risk of bone fractures in Medalists compared to non-diabetic peers. Additionally, the association with cardiovascular disease, demonstrates the BMD differences in group is likely not due to glycemic control alone.